Multivariate modulation and coding for wireless communication. - Raleigh, G.G (IEEE Journal on selected areas in communications)
This paper explores the improvement in information capacity and practical data rate that is possible with adaptive antenna technology applied to wireless-multipath communication channels. Whereas the conventional view is that multipath-signal propagation is an impediment to reliable communication, this paper shows that multipath can actually multiply the achievable data rate for wireless channels provided that the appropriate communication structure is employed. Multivariate discrete multitone (MDMT) combined with multivariate trellis-coded modulation (MTCM) is proposed and analyzed as a practical means of realizing a multiplicative-rate advantage in the case where channel-state information is not available at the transmitter. In Rayleigh fading, these new techniques are shown to simultaneously achieve a multiplicative data-rate advantage and lower error rate as compared to conventional coded orthogonal-frequency division multiplexing. Optimal minimum mean square error (MMSE), adaptive MDMT channel-estimation techniques are derived. The effects of channel-estimation error on MTCM are analyzed